Temperature Variation on the Central Tibetan Plateau Revealed by Glycerol Dialkyl Glycerol Tetraethers From the Sediment Record of Lake Linggo Co Since the Last Deglaciation - He, Yue; Hou, Juzhi; Wang, Mingda; Li, Xiumei; Liang, Jie; Xie, Shuyun; Jin, Yurong (Frontiers in Earth Science, 2020)
The Tibetan Plateau (TP) has numerous glaciers that provide water for more than one-third of the world’s population. Reconstructing past temperature change on the TP provides a valuable context for assessing the current and possible future status of glaciers. However, the quantitative paleotemperature records since the last deglaciation on the TP are sparse. Moreover, existing records have revealed a conflicting Holocene temperature variation patterns on the northeastern and western TP. Quantitative temperature records on the central TP would be essential for a better understanding of the spatiotemporal complexity of temperature variation. In this study, we report the temperature record from the sedimentary record of lake Linggo Co on the central TP since the last deglaciation using branched glycerol dialkyl glycerol tetraethers (bGDGTs) based proxy. Our results indicate that the paleoclimate during the last deglaciation on the central TP was characterized by large fluctuations in temperature. The mean annual temperature of lake Linggo Co remained low during the early Holocene (11.7–10 ka BP) and gradually increased to 4 oC at 8.3 ka, rapidly declining to -2 oC on average towards the present day. Solar radiation, continental glacier feedback, as well as atmosphere circulation play a major role in the distribution of sensitive and latent heat, thus affecting the Holocene temperature variability of the TP. Discrepancies in published records on the TP can result from a seasonal bias of the proxies and spatial differences due to topography - boundary effect. Our results suggest that the seasonal bias of proxies, the spatiotemporal difference should be taken into consideration before regional or global synthesis of paleotemperature records.